2010
DOI: 10.1007/s10238-009-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

CK20 and Ki-67 as significant prognostic factors in human bladder carcinoma

Abstract: Aberrant expression of CK20 and Ki-67 has been documented in many kinds of primary tumors and has proved useful as an ancillary diagnostic aid for those tumors. The aim of this study was to analyze the expression patterns of CK20 and Ki-67 in human bladder carcinomas (BCa) and to evaluate their clinical significance in the progression of BCa. CK20 and Ki-67 expression in BCa and normal bladder tissues were detected by immunohistochemical staining. The Spearman correlation was calculated between the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In our experimental model, altered CK14/20 staining was associated with multiple preneoplastic and neoplastic lesions. This agrees with the findings from clinical studies correlating aberrant CK14/20 staining with worsened prognostic in patients with bladder cancer (Ramos et al 2003;Ye et al 2010;Volkmer et al 2012;Otto et al 2013). The present results may also support the use of CK20 for distinguishing neoplastic and preneoplastic foci from some reactive lesions, as previously proposed (Edgecombe et al 2012;Amin et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our experimental model, altered CK14/20 staining was associated with multiple preneoplastic and neoplastic lesions. This agrees with the findings from clinical studies correlating aberrant CK14/20 staining with worsened prognostic in patients with bladder cancer (Ramos et al 2003;Ye et al 2010;Volkmer et al 2012;Otto et al 2013). The present results may also support the use of CK20 for distinguishing neoplastic and preneoplastic foci from some reactive lesions, as previously proposed (Edgecombe et al 2012;Amin et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Ramos et al (2003) described an association between increased CK20 expression and disease recurrence in patients with low-grade papillary tumours. Aberrant CK20 expression was also correlated with increased Ki-67 counts, as well as with tumour stage, histological grade, the presence of metastasis and reduced progression-free survival (Ye et al 2010). Otto et al (2013) recently reported that increased CK20 expression correlated with shorter recurrence-free survival in patients with T1 urothelial bladder carcinoma.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Using biopsy specimens, previous studies have identified certain immunomarkers as potential predictive markers for recurrence or as prognostic indicators of the severity of disease. Among these markers, p53 and Ki‐67 have been investigated in detail . Ki‐67 is a nuclear antigen present in all cycling human cells and is a marker of active cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Rajcani et al, (2013) found that CK20 was present in all invasive tumors. Ye et al, (2010) demonstrated that the intensity of CK20 and Ki-67 staining in cancerous tissues was significantly associated with tumor grades and distant metastasis of cancer bladder. Moreover, Bertz et al (2014b) suggested that the CK20 was a reliable indicator of biologic aggressiveness and may contribute to decision making on therapeutic strategy for pT1 bladder carcinomas.…”
Section: Discussionmentioning
confidence: 97%